Simultaneous detection of genomic imbalance in patients receiving preimplantation genetic testing for monogenic diseases (PGT-M) - Yang, Lin; Xu, Yan; Xia, Jun; Yan, Huijuan; Ding, Chenhui; Shi, Qianyu; Wu, Yujing; Liu, Ping; Pan, Jiafu; Zeng, Yanhong; Zhang, Yanyan; Chen, Fang; et al. (Frontiers in Genetics, 2022)
Background Preimplantation genetic test for monogenic disorders (PGT-M) has been used to select genetic disease-free embryos for implantation during in vitro fertilization (IVF) treatment. However, embryos tested by PGT-M have risks of chromosomal aneuploidy. Hence, a universal method to detect monogenic diseases and chromosome abnormalities is required. Methods Here, we report a novel PGT-A/M procedure allowing simultaneous detection of monogenic diseases and chromosomal abnormalities in one experiment. Library was prepared in a special way that multiplex polymerase chain reaction (PCR) was integrated into the process of whole genome amplification. The resulting library was used for one-step low-pass whole-genome sequencing (WGS) and high-depth target enrichment sequencing (TES). Results The TAGs-seq PGT-A/M was first validated with genomic DNA (gDNA) and the multiple displacement amplification (MDA) products of a cell line. Over 90% of sequencing reads covered the whole-genome region with around 0.3-0.4× depth, while around 5.4-7.3% of reads covered target genes with >10000× depth. Then, for clinical validation, 54 embryos from 8 women receiving PGT-M of β-thalassemia were tested by the TAGs-seq PGT-A/M. In each embryo, an average of 20.0 million reads with 0.3× depth of the whole-genome region was analyzed for chromosome abnormality, while an average of 0.9 million reads with 11260.0× depth of the target gene HBB were analyzed for β-thalassemia. Eventually, 18 embryos were identified with chromosome abnormality with 81.1% consistency to karyomapping results. 10 embryos contained β-thalassemia with 100% consistency to conventional PGT-M method. Conclusions TAGs-seq PGT-A/M simultaneously detected embryo chromosome abnormality and monogenic disease without dramatic increase of sequencing data output.